Thermodynamic analysis and simulation of combined adsorption heating and cooling system (2012)
This paper presents the description and thermodynamic analysis of a new hybrid system of solarpowered water heater and adsorption ice maker. Mathematical models were generated based on heat transfer in the collector, heat and mass transfer within the adsorbent-adsorbate pair and the thermodynamics of the adsorption process. The numerical models developed from finite difference transformation of the resulting equations were developed into a MATLAB computer code for easy implementation on a personal computer. The results reveal the ability of the hybrid system to heat 50kg water to about 96°C as well as produce ice at 7.2kg per day with a 2m2 evacuated vacuum-tube- type solar collector, with a coefficient of performance of 0.62. The system is capable of reaching a specific refrigeration density of 0.48kg ice per kg-adsorbent per day. Details on the effect of condensation, evaporation and adsorption temperature on the system coefficient of performance are also reported.